Madeleine Halmøy: The Norwegian Nominal System. A Neo-Saussurean Perspective. - Börjars, Kersti (Norsk Lingvistisk Tidsskrift, 2019)
Much has been written about Norwegian noun phrases, or those of the Scandinavian languages in general, including several book-length treatments within different theoretical models (Lødrup 1989, Delsing 1993, Börjars 1998, Julien 2005), still the book under review here offers a truly original perspective on the topic. The book is a slightly revised version of the author’s PhD thesis from University of Tromsø, and according to the author, the book ’presents a unified, economic account of the intricate relationship between form, meaning and interpretation in the Norwegian Nominal System, in its own right and on its own terms.’ (p. 1) The approach taken is described as ’Post-chomskyan Bouchardian Neo-Saussurean’ (p. 3).